Serum metabolite profiles of thyroid autoimmunity patients in early pregnancy - Zhaoying Chen; Zhenyu Lin; Yiyang Gao; Xiaohui Jin; Kan Chen; Chenxi Zhang; Zhongyan Shan; Weiping Teng; Jing Li (PeerJ)
Background Research on serum metabolite profiles in thyroid autoimmunity (TAI) patients during early pregnancy is currently limited. Aim & Methods The current study aimed to identify differential serum metabolites and assess the relationship between pregnancy outcomes and metabolic abnormalities in individuals with TAI. This research included 26 pregnant women with TAI and 30 healthy controls (HC). We employed a liquid chromatograph mass spectrometer (LC-MS) to analyze changes between the two groups. Results Newborns in the TAI patients had lower birth weights than those in the control group (P = 0.007). We identified 92 differential metabolites (including 50 upregulated and 42 downregulated) belonging to amino acids, fatty acyls, glycerophosphocholines, steroid and other categories and four significantly enrichment Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways including taurine and hypotaurine metabolism, citrate cycle (TCA cycle), glyoxylate and dicarboxylate metabolism and 2-oxocarboxylic acid metabolism. We further identified 15 characteristic metabolites (6-Methylquinoline, D-erythrose 4-phosphate, 4-Hydroxyisoleucine, phosphatidylcholine (PC)(16:2e/16:0), N3,N4-Dimethyl-L-arginine, N-desmethyltramadol, 3-Methoxybenzaldehyde, sphingomyelin (SM)(d14:3/28:2), gamma-Glutamylleucine, NSI-189, 3-(1-cyano-1,2-dihydroisoquinolin-2-yl)-3-oxopropyl propionate, lysophosphatidylinositol (LPI) 16:0, cis-Aconitic acid, polyamide (PA)(18:1/18:2) and fatty acyl esters of hydroxy fatty acid (FAHFA)(17:0/18:0)) using least absolute shrinkage and selection operator (LASSO) regression. Correlation analyses revealed that 6-Methylquinoline, D-erythrose 4-phosphate, gamma-Glutamylleucine, and LPI 16:0 exhibited a positive correlation with anemia before delivery, while 3-(1-cyano-1,2-dihydroisoquinolin-2-yl)-3-oxopropyl propionate had a negative correlation. LPI 16:0 displayed a positive correlation with uric acid (UA) during both middle and late pregnancy, whereas 3-Methoxybenzaldehyde exhibited a negative correlation with UA in late pregnancy. Cis-Aconitic acid showed a positive correlation with fasting blood glucose (FBG) in middle pregnancy. Conversely, 6-Methylquinoline and 4-Hydroxyisoleucine had a negative correlation with birth weight. Thyroid autoantibodies were found to be associated with 14 metabolites identified using LASSO, with the exception of PA (18:1/18:2). Conclusions Our findings provide new evidence supporting the early screening of serum metabolites and their potential for predicting adverse pregnancy outcomes in women with TAI.